(untitled) (International Engineering Journal For Research & Development, 2020)
Today, ideological threats are manifested in the form of attempts to change the views of certain segments of the population, especially young people, in the direction that suits them, to absorb destructive ideas, such as religious extremism and immorality. In today's dangerous world, it is clear that every conscientious person is worried about malicious information spread on the Internet, various destructive ideas and vile vices that undermine morality. Since the second half of the twentieth century in the world, the popularization of computers and Internet communications has led to the emergence of a number of socio-economic problems at the beginning of the XXI century, along with the impact on all aspects of human practice, in particular on religious processes. Throughout human history, the speed and importance of data transfer have been one of the main tools for making cyberspace as popular as it is today. Therefore, the study of religious and spiritual processes related to cyberspace and plays an important role. Today, ideological threats are manifested in the form of attempts to change the views of certain segments of the population, especially young people, in the direction that suits them, to absorb destructive ideas, such as religious extremism and immorality. In today's dangerous world, it is clear that every conscientious person is worried about malicious information spread on the Internet, various destructive ideas and vile vices that undermine morality[1].